2020
DOI: 10.1186/s12879-020-05549-8
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic changes in virology, specific antibody response and imaging during the clinical course of COVID-19: a descriptive study

Abstract: Background To explore the kinetic changes in virology, specific antibody response and imaging during the clinical course of COVID-19. Methods This observational study enrolled 20 patients with COVID-19, who were hospitalized between January 20–April 6, 2020, in the two COVID-19 designated hospitals of Zhoushan, Zhejiang and Rushan, Shandong, China, The laboratory findings, imaging, serum response to viral infection, and viral RNA lev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The duration of symptoms in patients who were readmitted (median 5 days) was shorter than in those who were not readmitted (IQR) (7 days, < 0.001, Table 2 ). The prolonged clinical course with frequent worsening that characterizes moderate and severe forms of the disease suggests that the time of onset of the patient's symptoms should be taken into account when considering hospital discharge 20 , 21 . A shorter duration of index admission has been associated with a higher risk of readmission 6 , 7 ; a result that has not been observed in our series.…”
Section: Discussionmentioning
confidence: 99%
“…The duration of symptoms in patients who were readmitted (median 5 days) was shorter than in those who were not readmitted (IQR) (7 days, < 0.001, Table 2 ). The prolonged clinical course with frequent worsening that characterizes moderate and severe forms of the disease suggests that the time of onset of the patient's symptoms should be taken into account when considering hospital discharge 20 , 21 . A shorter duration of index admission has been associated with a higher risk of readmission 6 , 7 ; a result that has not been observed in our series.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al reported that SARS-CoV-2 RNA was maintained for 42 days in pharyngeal and sputum samples ( 3 ). In the case of patients in our hospital, viral shedding was maintained until the 18th day from symptom onset in the mildly affected group, and shedding continued until the 33rd day from symptom onset in the severely affected group.…”
Section: Discussionmentioning
confidence: 99%
“…The viral load rises during the first week of infection and gradually decreases over the next few days. SARS CoV-2 antibodies start to rise 10 days after infection, and most patients become seroconverted within the first twenty days [49] .…”
Section: Covid-19mentioning
confidence: 99%